A Mixed-Methods Analysis of Critical Thinking Skills and Contributing Factors: The Case of Indonesian Pre-service Biology Teachers - Astutik, Fuji; Ruswan, Ruswan; Mindiana, Agnes Tasya; Wijayanti, Erna (FKIP Universitas Lampung, 2025)
The purpose of this study was to measure the critical thinking skills of student teachers and the factors influencing them. The survey involved 477 participants from an Islamic university, including six lecturers. Data were collected in three stages. The level of critical thinking skills was measured using a test whose items were developed based on the Watson-Glaser Critical Thinking Appraisal (WGCTA) indicators. The study also reviewed lesson plans, student worksheets, and cognitive test questions. Interviews were conducted with four students from each year, the highest- and lowest-skilled, as well as with six lecturers. A one-way ANOVA was used to examine differences in critical thinking skills across university study lengths. Qualitative data were analyzed using content analysis methods. The study's findings indicated that four groups had critical thinking skills in the